Effectiveness assessment and spatial distribution characteristics of helium source rocks in the Shixi Block along the eastern margin of the Ordos Basin - Yangmei CHANG; Chao LIU; Beilei SUN (Meitian dizhi yu kantan)
BackgroundHelium gas serves as a significant rare strategic resource. In China, helium resources are relatively scarce and dependent heavily on imports. Therefore, there is a pressing need for the exploration and exploitation of helium resources. Helium source rocks provide a material basis for the formation of helium resources. The Zijinshan pluton serves as a principal source of coal-measure helium along the eastern margin of the Ordos Basin. Previous studies reveal that helium in natural gas within the Shixi Block originates primarily from the decay of radioactive elements in the deep part of the Jianjiagou-Zijinshan plutons. However, there is a lack of reports on the discovery of helium-rich natural gas in the Linxing Block, which is closer to the Zijinshan pluton. MethodsThis study investigated the Linxing and Shixi Blocks as study areas. Utilizing the geochemical parameters and mineralogical characteristics of helium source rocks in these blocks, this study quantitatively analyzed the helium-generating intensities of the helium source rocks, assessed their effectiveness, and calculated their helium generation volumes. In combination with log data, this study investigated the spatial distribution characteristics of potential helium source rocks in the Shixi Block along the eastern margin of the Ordos Basin.Results and Conclusions The potential helium source rocks in the Shixi Block exhibit uranium (U) content ranging from 0.25×10−6 to 9.19×10−6 and thorium (Th) content from 0.56×10−6 to 21.0×10−6. In contrast, potential helium source rocks in the Linxing Block manifest U content ranging from 1.29×10−6 to 207×10−6 and Th content from 8.19×10−6 to 438×10−6. Within the Shixi and Linxing blocks, U and Th occur predominantly as isomorphism in the basement granites. In bauxites, mudstones, coals, and sandstones, U and Th occur primarily in adsorbed and complexed forms, associated with organic matter and clay minerals. The Shixi and Linxing blocks have total helium generation volumes ranging from 4.92×108 m3 to 6.94×108 m3 and from 75.7×108 m3 to 110.4×108 m3, respectively. Primary helium source rocks in the Shixi Block include the metamorphic series and granites in the basement, followed by dolomites, sandstones, mudstones and coals. In contrast, primary helium source rocks in the Linxing Block encompass the metamorphic series and granites in the basement, along with the Zijinshan pluton, succeeded by dolomites, sandstones, mudstones, coals, and bauxites. Given the lack of log data, this study failed to analyze the spatial distribution characteristics of helium source rocks in the Linxing Block. However, the calculated helium generation volumes suggest the exploration and exploitation potential throughout the Linxing Block. The helium source rocks in the Shixi Block (except for the basement) are thick in the western and thin in the eastern portions. Notably, both sandstones in the lower Shihezi Formation and most strata in the Shanxi Formation exhibit high helium generation volumes. Therefore, these strata should be highlighted in the exploration and exploitation of helium resources.